MOMCILO TAPAVICA Life and work in Montenegro - Dimitrije Rašović; Nenad Zivanovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
At the end of 19 centery tennis started to play at palace of grand duke Nikola in Cetinje. Montenegrian Momcilo Tapavica who was participat at first modern Olimpic games in Atina at 1896, gave great contribution developed tennis sport in Montenegro. Tapavica come to palase of graund duke's Nikola at 1902 and ofter that date his family moved to Herceg - Novi where they spent all time until second world war. At the first Olimpic games Tapavica took part in these sports: tennis, weightlifting, wrestling. Certain he was a talented athlete has made a great contribution not only to the development of tennis but other sports development in Montenegro.